2014
DOI: 10.1007/s13197-014-1663-5
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic index and quality evaluation of little millet (Panicum miliare) flakes with enhanced shelf life

Abstract: Little millet is a minor cereal crop contains several nutraceutical components. Ready To Cook (RTC) flakes of the millet exhibited higher total dietary fiber content (22.40 %) compared to dehulled grain (15.80 %). One serving (30 g) of RTC flakes provided 2.25 g of protein, 0.13 g of fat, 0.13 g of total minerals, 9.67 mg of iron and zero trans fats. The flakes possessed a medium Glycemic Index (GI) of 52.11 ranging from 41.57 to 61.80 among normal volunteers. Glycemic Load (GL) of the flakes was a low of 9.24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 11 publications
(11 reference statements)
1
21
0
Order By: Relevance
“…1). Similar findings was reported by Patil et al (2014) in little millet flakes. The stored little millet RTC flakes indicated that sensory profile in the form of wet avalakki decreased during storage period however the product was acceptable upto 4 months of storage with an acceptability index of 76.66 (Table 5).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…1). Similar findings was reported by Patil et al (2014) in little millet flakes. The stored little millet RTC flakes indicated that sensory profile in the form of wet avalakki decreased during storage period however the product was acceptable upto 4 months of storage with an acceptability index of 76.66 (Table 5).…”
Section: Resultssupporting
confidence: 91%
“…This could be due to better physical attribute of little millet flakes (Table 2). Patil et al (2014) reported RTC little millet avalakki exhibited an acceptability index of 81.11. Ragi avalakki was not attractive (6.12) due to the dark hues (Table 1) and the panelists opined that it exhibited fibrous texture and was chewy with a mean total score of 29.99 and acceptability index of 66.64..…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations